2016
DOI: 10.4103/2277-9175.176366
|View full text |Cite
|
Sign up to set email alerts
|

Association between two common polymorphisms (single nucleotide polymorphism -250G/A and -514C/T) of the hepatic lipase gene and coronary artery disease in type 2 diabetic patients

Abstract: Background:Variations in the hepatic lipase (HL) gene are the potential candidate for coronary artery disease (CAD) especially in type 2 diabetes mellitus (T2DM) in diverse populations. We assessed the association of -514C/T and -250G/A polymorphisms in HL (LIPC) gene with CAD risk in Iranian population with type 2 diabetes.Materials and Methods:We evaluated 322 type 2 diabetic patients, 166 patients with normal angiograms as controls and 156 patients those identified with CAD undergoing their first coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…CAD develops as a result of vascular tract stenosis or occlusion caused by coronary atherosclerotic lesions and several environmental and lifestyle factors (Campbell et al, 1998;Erbel and Görge, 2014;Bullock-Palmer, 2015). Previous experimental studies at the molecular level have indicated that many genetic factors, including the genes encoding angiotensinogen and angiotensin-converting enzyme, hepatic lipase, insulin receptor substrate-1, kinesin family member 6, cholesteryl ester transfer protein, ATP-binding cassette subfamily A member 1, and apoptotic extrinsic death receptor, have an important role in the risk of CAD development (Bonfim-Silva et al, 2016;Cyrus et al, 2016;Kishore Kumar et al, 2016;Mohammadzadeh et al, 2016;Vatte et al, 2016;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…CAD develops as a result of vascular tract stenosis or occlusion caused by coronary atherosclerotic lesions and several environmental and lifestyle factors (Campbell et al, 1998;Erbel and Görge, 2014;Bullock-Palmer, 2015). Previous experimental studies at the molecular level have indicated that many genetic factors, including the genes encoding angiotensinogen and angiotensin-converting enzyme, hepatic lipase, insulin receptor substrate-1, kinesin family member 6, cholesteryl ester transfer protein, ATP-binding cassette subfamily A member 1, and apoptotic extrinsic death receptor, have an important role in the risk of CAD development (Bonfim-Silva et al, 2016;Cyrus et al, 2016;Kishore Kumar et al, 2016;Mohammadzadeh et al, 2016;Vatte et al, 2016;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hou et al demonstrate that subgroup analyses based on ethnic group illuminated that +45T>G polymorphism is significantly associated with CAD risk among Arabians, with an overall ORs (95% CIs) of 1.65 (1.12‐2.42) for allelic frequency. However, in the same meta analysis, only three populations showed no association with CAD from the eight studied Arab populations including 2306 Arabians …”
Section: Discussionmentioning
confidence: 92%
“…First, Esteghamati et al on a study of 114 type 2 diabetic subjects with CAD, and 127 type 2 diabetic patients without CAD revealed that two haplotypes 45T‐276T and 45G‐276T were associated with a decreased risk of CAD [adjusted OR = 0.47 (95% CI: 0.32–0.94); P = .03 and adjusted OR = 0.33 (95% CI: 0.13–0.83); P = .02, respectively]. Second, Mohammadzadeh et al found that the haplotype consisting of mutant allele of SNP +45 and wild allele of SNP +276 was more prevalent in CAD cases compared to the controls (OR = 0.37, 95% CI = 0.16‐0.86, P = .022).…”
Section: Discussionmentioning
confidence: 99%
“…The genotyping of ADIPOQ polymorphisms (−3971A/G and +276G/T) was performed using polymerase chain reaction–based restriction fragment length polymorphism (PCR‐RFLP) methods. The primers and restriction enzymes used were taken from previously reported studies and are listed in Table (Mohammadzadeh, Ghaffari, Heibar, & Bazyar, ; Ramya et al., ).…”
Section: Methodsmentioning
confidence: 99%